ORANG LAUT – BAJAK LAUT – RAJA LAUT: TEORI ADRIAN B. LAPIAN DALAM POLA MASYARAKAT MARITIM KERAJAAN SRIWIJAYA - Mulyanto, Heru (UI Scholars Hub, 2025)
This short article attempts to apply Adrian B. Lapian's theory of three maritime community groups (Sea People, Pirates, & Sea Kings) in the context of the Srivijaya Kingdom other than the Sulu Islands which are the focus of Lapian's discussion. This article analyzes the involvement of the king in the recruitment of Pirates and the organizational structure of Pirates and Sea Kings in Srivijaya. Meanwhile, the Sea People group in the Srivijaya Kingdom is analyzed here by identifying their roles in trade and cooperation with Sea Raiders and Sea Lords according to Adrian B. Lapian's previous theory from the case study of the Sulu Sultanate. It was found that the novelty of the study was that there was a comparison of cases in the Riau-Bangka Belitung Islands Sea Region with the Sulawesi Sea and Sulu Islands in terms of the loyalty of the Sea People in Sulu and Srivijaya (Riau-Bangka Islands). Likewise, the organizational structure of the Sea Kings and the Pirate recruitment system in both regions had significant differences. This study uses a historical method that has four stages, namely heuristics, criticism, verification, and historiography.